Educational Values in The Novel 'Sepatu Dahlan' by Khrisna Pabichara - Abdulloh Abdulloh; Fransisca S.O. Dedi; Dinda Adelia (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2023)
The issues in this research are related to the messages conveying educational values of diversity, resilience, holistic intelligence (identity discovery), responsibility, attitude towards life, and poverty found in literary works (novels). This study aims to identify and analyze the educational values, namely diversity, resilience, holistic intelligence (identity discovery), responsibility, attitude towards life, and poverty, present in the novel